Variability in dynamic daylight simulation in clear sky conditions according to selected weather file: Satellite data and land-based station data - Monteoliva, Juan Manuel (2015)
While the use of satellite weather files is a possibility in regions without terrestrial stations, it is necessary to consider their impact on daylight simulations. This paper aims to verify the variability of dynamic daylight simulation results according to the weather file used. This study compares the results of daylight simulations in learning spaces using different weather files (land-based station data - satellite data). This work is divided in three main stages: comparative analysis of climatic databases; comparative analysis of annual outside horizontal illuminance; analysis of dynamic daylight performance metrics. Annual calculated dynamic daylight metric indicates variations of up to 13% under the different weather files analyzed. This is a relevant topic since the accurate prediction of daylight levels for indoor environments guides daylighting design.